Tantangan Tata Kelola Pemerintahan Dalam Penataan Ruang Terbuka Hijau: Studi Kasus Kabupaten Enrekang - Lamading, Emilia Zafira; Nurlinah, Nurlinah; Saharuddin, Saharuddin (Development Policy and Management Review (DPMR), 2025)
The arrangement and management of green open spaces (RTH) is an important part of regional spatial planning policies that focus on sustainable development and improving the quality of public services. This study aims to apply the principles of good governance participation, accountability, effectiveness, efficiency, and transparency in governance in the management of green open spaces in Enrekang Regency. The study used a qualitative descriptive approach with data collection techniques through in-depth interviews, field observations, and reviews of regional planning documents. Data were analyzed using inductive reduction, presentation, and conclusion techniques. The results show that the application of good governance principles in the arrangement of green open spaces in Enrekang Regency is not optimal. The aspect of community participation is still symbolic because community involvement occurs more at the socialization stage than in substantive planning. Accountability for program implementation has not been measured transparently, especially in budget management and reporting of activity results. In addition, program effectiveness is hampered by limited human resource capacity and coordination between local government institutions. Despite the regional government's commitment to expanding green open space (GOS) as mandated by Law Number 26 of 2007 concerning Spatial Planning, its implementation still faces structural and institutional challenges. This study recommends strengthening environmental governance institutions by expanding meaningful public space participation, increasing transparency in planning and budgeting processes, and establishing a performance-based evaluation system to ensure the sustainability of GOS policies. These findings emphasize the importance of integrating good governance and environmental policies to improve the quality of public services and community welfare at the regional level.     Abstrak Penataan dan pengelolaan ruang terbuka hijau (RTH) merupakan bagian penting dari kebijakan tata ruang daerah yang berorientasi pada pembangunan berkelanjutan dan peningkatan kualitas pelayanan publik. Penelitian ini bertujuan untuk mengevaluasi penerapan prinsip-prinsip good governance partisipasi, akuntabilitas, efektivitas, efisiensi, dan transparansi dalam tata kelola pemerintahan pada pengelolaan RTH di Kabupaten Enrekang. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi lapangan, serta telaah dokumen perencanaan daerah. Data dianalisis menggunakan teknik reduksi, penyajian, dan penarikan kesimpulan secara induktif. Hasil penelitian menunjukkan bahwa penerapan prinsip good governance dalam penataan RTH di Kabupaten Enrekang belum optimal. Aspek partisipasi masyarakat masih bersifat simbolik karena keterlibatan publik lebih banyak terjadi pada tahap sosialisasi daripada pada perencanaan substantif. Akuntabilitas pelaksanaan program belum terukur secara transparan, terutama dalam pengelolaan anggaran dan pelaporan hasil kegiatan. Selain itu, efektivitas program terhambat oleh keterbatasan kapasitas sumber daya manusia dan koordinasi antarlembaga pemerintah daerah. Walaupun terdapat komitmen pemerintah daerah dalam memperluas RTH sesuai amanat Undang-Undang Nomor 26 Tahun 2007 tentang Penataan Ruang, pelaksanaannya masih menghadapi kendala struktural dan kelembagaan. Penelitian ini merekomendasikan perlunya penguatan kelembagaan tata kelola lingkungan dengan memperluas ruang partisipasi publik yang bermakna, meningkatkan transparansi dalam proses perencanaan dan penganggaran, serta membangun sistem evaluasi berbasis kinerja untuk memastikan keberlanjutan kebijakan RTH. Temuan ini menegaskan pentingnya integrasi antara tata kelola pemerintahan yang baik dan kebijakan lingkungan dalam rangka peningkatan kualitas pelayanan publik dan kesejahteraan masyarakat di tingkat daerah.